SP0237 An Overview of Quality Indicators for the Management of Osteoarthritis in Primary Care. (9th June 2015) - Edwards, J.J.
Abstract : Consultations for osteoarthritis occur commonly in primary care with up to 11% of older adults consulting for OA annually. Studies have consistently identified shortcomings in OA management in the community. However there is no systematically implemented set of quality indicators for OA care unlike for many other long term conditions that are, for example, represented in the UK Quality & Outcomes Framework (QOF). We performed a systematic review and narrative synthesis of studies that have developed and tested OA quality indicators and identified 15 indicators that were considered valid and feasible for routine use in primary care [1]. These covered domains including holistic assessment, education, exercise, weight loss, assistive devices, pharmacological management, and specialist assessment. The indicators were consistent with the OA guidance from EULAR and NICE, though not all recommendations had published indicators identified. Some indicators may be measured from routinely-recorded data in primary care. We included those not measurable through routine data in a new electronic recording template as part of the MOSAICS study [2]. The template was installed in 8 general practices and was triggered when the health care professional entered a morbidity code for OA. An evaluation study showed that it was feasible to use such a template to measure the quality of OA care. Assessment indicators were well-captured but, for example, consideration of physiotherapy was less so. An increase in some routinely recorded indicators (weight recording and prescription of paracetamol and topical NSAIDs was also seen after the template was introduced [3]. The recording template and associated indicators are now being introduced to other general practices as a part of routine care [4]. Quality indicators are a necessary and valid tool to improve the quality of primary care for OA. Their use in consultations as a prompt and recording template is feasible and is associated with improvements in some aspects of recording and management. There remains a need to address uptake of non-pharmacological management and to address variation between clinicians. Inclusion of indicators in a routine and systematic way such as through the QOF would be a logical next step in the drive to enhance OA care in primary care. References: Edwards JJ, Khanna M, Jordan KP, Jordan JL, Bedson J, Dziedzic KS. Quality indicators for the primary care of osteoarthritis: a systematic review. Ann Rheum Dis 2013 (Published On-line First: 27 November 2013) doi: 10.1136/annrheumdis-2013-203913. Dziedzic KS, Healey EL, Porcheret M, Ong B, Main CJ, Jordan KP, et al. Implementing the NICE osteoarthritis guidelines: a mixed methods study and cluster randomised trial of a model osteoarthritis consultation in primary care - the Management of OsteoArthritis In Consultations (MOSAICS) study protocol. Implement Sci 2014;9(1):95 doi: 10.1186/s13012-014-0095-y. Edwards JJ, Jordan KP, Peat G, Bedson J, Croft PR, Hay EM, et al. Quality of care for OA: the effect of a point-of-care consultation recording template. Rheumatology 2014 doi: 10.1093/rheumatology/keu411. Research Institute for Primary Care & Health Sciences. The OA e-template. 2015. www://www.keele.ac.uk/pchs/disseminatingourresearch/researchtools/oae-template/ Disclosure of Interest: J. Edwards Employee of: General Practitioner, providing general medical services and benefitting financially from the Quality & Outcomes Framework